2001
DOI: 10.1046/j.0962-1083.2001.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of indigenous Rhizobium leguminosarum bv. viciae isolates nodulating two different host plants during soil restoration with alfalfa

Abstract: A total of 360 Rhizobium leguminosarum bv. viciae strains was isolated from three brown-coal mining restoration fields of different age and plant cover (without and in the first and second year of alfalfa, Medicago sativa, cultivation) using two host species (Vicia hirsuta and Pisum sativum) as capture plants. The strains were genetically typed by restriction fragment length polymorphism analysis of polymerase chain reaction (PCR)-generated 16S-23S ribosomal DNA intergenic spacer regions (IGS-RFLP) and charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Correlations between chromosomal and Sym plasmid genotypes have been previously observed within pea R. leguminosarum bv. viciae populations (11,23,50,52). This suggests that both components of the rhizobial genome are involved in competitiveness for nodule formation with peas.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Correlations between chromosomal and Sym plasmid genotypes have been previously observed within pea R. leguminosarum bv. viciae populations (11,23,50,52). This suggests that both components of the rhizobial genome are involved in competitiveness for nodule formation with peas.…”
Section: Discussionmentioning
confidence: 91%
“…A previous study has shown that associations constructed by introduction of the same Sym plasmid in different recipient strains varied in competitiveness for nodulation of pea plants, indicating that both components of the genome were involved (5). Several reports have shown that the Sym plasmid is not strictly associated with the chromosomal background in natural populations of R. leguminosarum (14,23,25,30,38,50,52). The analysis of the genetic structure of populations of R. leguminosarum bv.…”
mentioning
confidence: 99%
“…About 120 transformants were randomly selected for each straw sample in black soil and subjected to restriction fragment length polymorphism (RFLP) analysis (40). To do this, the cloned 16S rRNA gene fragments were PCR amplified using two primers located in the vector, RV-M (5=-GAGCGGA TAATTTCACACAGG-3=) and M13-47 (5=-CGCCAGGGTTTTCCCAG TCACGA-3=), and PCR products were digested by two enzymes, Sau3AI and HhaI.…”
Section: Experimental Setup Of Soil Transplantation and Straw Decompomentioning
confidence: 99%
“…Cultivated areas containing Neonotonia wightii (Lopes et al, 1972), peanut (Giardini et al, 1985;Lombardi et al, 1992) or green manure legumes (Chada & De Polli, 1988;Rodrigues et al, 1994, Zilli et al, 2004 were capable of maintaining rhizobial communities that were highly infective for their host plants and well adapted to soil conditions. Several studies indicated that the rhizobial communities can be affected by the properties of the soil and by the host plants (Palmer & Young, 2000, Zhang et al, 2001Laguerre et al, 2003), as well as by soil tillage (Cattelan & Vidor, 1990;Castro et al, 1993, Carvalho et al, 2004, and crop history (Venkatesvarlu et al, 1997).…”
Section: Introductionmentioning
confidence: 99%